2016
DOI: 10.1371/journal.pone.0166666
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Visual Fields in Patients with Retinitis Pigmentosa Using a Novel Microperimeter with Eye Tracking: The MP-3

Abstract: PurposeThe purpose of the current study is to investigate the test-retest reproducibility of visual fields (VFs) measured with the MP-3 microperimeter, in patients with retinitis pigmentosa (RP).MethodVFs were twice measured with the MP-3 and also the Humphrey Field Analyzer, using the 10–2 test grid pattern in both perimeters, in 30 eyes (15 right and 15 left eyes) of 18 RP patients (11 males and 7 females). Test-retest reproducibility was assessed using the mean absolute deviation (MAD) measure at all 68 poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…The fact that our study cohort also had no learning effects in conventional perimetry supports that hypothesis. Recently, Igarashi et al [18] published data investigating test-retest reproducibility of the MP-3 and Humphrey Field Analyzer (Carl Zeiss Meditec AG, Germany) in patients with retinitis pigmentosa (RP) and found a high reproducibility for both devices, but slightly lower ICC values as compared to our study. RP patients are usually not that experienced in visual field testing and in advanced stages of RP visual fields are reduced to a central island of visual field.…”
Section: Discussionsupporting
confidence: 44%
“…The fact that our study cohort also had no learning effects in conventional perimetry supports that hypothesis. Recently, Igarashi et al [18] published data investigating test-retest reproducibility of the MP-3 and Humphrey Field Analyzer (Carl Zeiss Meditec AG, Germany) in patients with retinitis pigmentosa (RP) and found a high reproducibility for both devices, but slightly lower ICC values as compared to our study. RP patients are usually not that experienced in visual field testing and in advanced stages of RP visual fields are reduced to a central island of visual field.…”
Section: Discussionsupporting
confidence: 44%
“…In this manner, we would expect to observe highly reproducible measurements of retinal sensitivity. 10 The microperimetry examination was performed in a dark room. All patients underwent a dark adaptation for at least half an hour until the pupil size reached 4mm or larger.…”
Section: Methodsmentioning
confidence: 99%
“…Controversy focused on the potential injury of ILM-peeling. Major side effects of ILM peeling have been reported as potential mechanical or functional injury to retina [2][3][4][5][6][7][8][9][10]. Previous studies about retinal functional changes that caused by ILM peeling are conflicting: a few authors found no changes after peeling [11,12], others showed decrease of retinal sensitivity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum luminance of the MP-3 is 10,000 asb, and the stimulus dynamic range is between 0 and 34 dB. [10][11][12][13][14] Only reliable test results (a false-positive rate of <20% and a false-negative rate of <25%) were used in the analyses, as in the HFV SITA test results set in the present study. A fixation loss is not applicable because the MP-3 has an autotracking system, making it possible to project the stimulus only at predefined retinal positions.…”
Section: Functional Dfr Angle Measurementmentioning
confidence: 99%
“…Clinical application of the MP-3 is increasing as it relates to evaluating glaucoma 12 and other eye diseases, such as retinitis pigmentosa. 13,14 Another issue that should be considered when assessing structure-function correlation is the parameter to be evaluated. Previously, either a disc-fovea (DF) angle or a TR angle, or both, were evaluated.…”
mentioning
confidence: 99%